ANALISIS STRATEGI BAURAN KOMUNIKASI PEMASARANDALAM MENINGKATKAN PENJUALAN SENJATA KERIS DIDESA AENG TONG – TONG SUMENEP - Andi Barri Albar; Suyono Suyono (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study aims to determine what strategies are used to increase the sale of keris weapons in the village of Aeng Tong-Tong Sumenep. The research method used is descriptive qualitative, descriptive research aims to collect detailed information by describing the situation in the field, data obtained through interviews with researchers from informants. From the results of research that can be obtained that the marketing communication mix that has been used by businessmen in the village of Aeng Tong-Tong Sumenep currently is Advertising, Sales promotion, Event and experiences, Online and social media marketing,interactive marketing, Personal selling. With the marketing communication mix relatively increased compared to before using only conventional sales methods.